Review of the genus Lecithocera Herrich-Schäffer (Lepidoptera, Lecithoceridae) in DR Congo, with description of four new species - Park, Kyu-Tek; Koo, Jun-Mo; Jeong, Su-Yeon; de Prins, Jurate; de Prins, Willy (Zootaxa, 2023)
The genus Lecithocera Herrich-Schäffer, 1853 in the Democratic Republic of the Congo (DR Congo) is reviewed, with descriptions of four new species: Lecithocera katangaica Park, sp. nov., L. seydeliella Park, sp. nov., L. cornutispina Park, sp. nov., and L. lusingensis Park, sp. nov. Five species are already recorded from this country: 1) L. chloroscia Meyrick described from DR Congo; 2) L. lucernata Meyrick previously reported from DR Congo by Ghesquière in 1940; 3) L. trifera Meyrick and 4) L. xanthochalca Meyrick, their generic assignments still remain doubtable; and 5) L. ideologa Meyrick. Lecithocera dicentropa Meyrick, 1938 is synonymized as a junior synonym of L. ideologa Meyrick. Adults and the genitalia of the new species and L. ideologa Meyrick are illustrated, and a lectotype for L. trifera Meyrick is designated herein.